Special Medical Food in Premature Child with Postnatal Malnutrition: Clinical Case - Irina А. Belyaeva; Elena P. Bombardirova; Tatiana V. Turti; Evgeniia A. Prikhodko ("Paediatrician" Publishers LLC, 2022)
Background. Protein-calorie deficiency is common multifactorial medical condition in infants. Nutrition therapy of protein-calorie deficiency in premature infants with special medical food is not always quite effective. It can be associated with residual manifestations of overlapping perinatal pathology.Clinical case description. Extremely premature child with severe protein-calorie deficiency in the late period with combined perinatal pathology (perinatal central nervous system damage and bronchopulmonary dysplasia) was administrated with therapeutic highly nutritious (high-protein/high-energy) milk formula according to individual plan. The positive dynamics in clinical manifestations of the main and associated diseases was noted on nutrition therapy.Conclusion. High-calorie and protein-enriched therapeutic formula can effectively correct protein-calorie deficiency in premature infants with associated perinatal pathology in the recovery period (disfunction compensation).